Global warming scenarios for the Eastern Adriatic Sea indicate a higher risk of invasiveness of non-native marine organisms relative to current climate conditions - Glamuzina, Branko; Vilizzi, Lorenzo; Piria, Marina; Žuljević, Ante; Cetinić, Ana Bratoš; Pešić, Ana; Dragičević, Branko; Lipej, Lovrenc; Pećarević, Marijana; Bartulović, Vlasta; Grđan, Sanja; Cvitković, Ivan; et al. (Marine life science & technology, 2024)
Globally, marine bioinvasions threaten marine ecosystem structure and function, with the Mediterranean Sea being one of the most affected regions. Such invasions are expected to increase due to climate change. We conducted a risk screening of marine organisms (37 fishes, 38 invertebrates, and 9 plants), both extant and ‘horizon’ (i.e., not present in the area but likely to enter it). Based on expert knowledge for the Eastern Adriatic Sea coasts of Slovenia, Croatia, and Montenegro, screenings were conducted under both current and predicted climate conditions indicating with an increase in sea surface temperature and salinity of the Adriatic Sea together with changes in precipitation regime. Our aims were to: (1) identify non-native extant and horizon marine species that may pose threats to native biodiversity and (2) evaluate the risk of invasiveness of the selected species under current and predicted climate conditions. Of the 84 species screened, there was an increase in those ranked as ‘high risk’ from 33 (39.3%) under current climate conditions and to 47 (56.0%) under global warming scenarios. For those ranked as ‘very high’ risk, the increase was from 6 (7.1%) to 21 (25.0%). Amongst the screened species, the already established high-risk species Pacific oyster Magallana gigas and Atlantic blue crab Callinectes sapidus represent a threat to ecosystem services. Given the under-representation of marine species in the current European Union List, the species we have ranked as high to very high risk should be included.